Development of Virtual Reality (VR) Media on Ecosystem and Environmental Materials Using the Problem Based Learning (PBL) Model to Improve Digital Literacy and Critical Thinking Skills in Biology Education Students - Satriya, Robby Nur; Sari, Murni Sapta; Munzil, Munzil (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2024)
This research was conducted at PGRI Argopuro University Jember to determine students' digital and critical thinking abilities using VR learning media. The learning model used in this research is problem-based learning in ecology courses. This research aims to explore the potential of VR learning media to answer the challenges of 21st century skills, namely digital skills and critical thinking skills, as well as providing innovative learning designs to universities. Media applications use ADDIE. Before being given treatment, respondents will fill out a digital skills pretest questionnaire and critical thinking skills pretest. The results of survey activities and Question Validation are valid, so you can distribute the survey and questions to your respondents. Validation activities carried out by material experts are 100% in the